Preventive conservation plan for library buildings in La Plata, Argentina - Diulio, María de la Paz (2015)
This summary shows the advances of a project called "Development of building environmental management and continuous monitoring for preventive conservation in UNLP libraries" which is now taking place in the libraries of the National University of La Plata. It is essential to know the hygrothermal condition inside the book deposits, as one of the first preventive measures to become aware of the state of conservation of the books. The aim of the study is to propose a systematic environmental monitoring method to verify compatibility between measured parameters and optimal preservation conditions. Annual monitoring campaign was performed in twelve libraries with diverse results according to the characteristics of the envelope and HVAC systems. It is the first time that a formal monitoring campaign has taken place in these library buildings. We met staff well disposed and eager to achieve better results. We provide a standard report model suitable for the institutions as a decision-making tool, with simultaneous analysis of temperature and relative humidity, according to the local climate.